Peran Sumber Daya Manusia dalam Strategi Content Marketing pada Produk Somethinc untuk Meningkatkan Kompetitif Bisnis Internasional - Zahrani Adhelia Putri (Pusat Riset dan Inovasi Nasional, 2025)
In the ever-growing digital era, content marketing strategy is an important key in increasing business competitiveness, especially in the highly competitive beauty industry. This research aims to analyze the role of human resources (HR) in implementing content marketing strategies for Somethinc products, a beauty brand from Indonesia that has succeeded in penetrating the international market. The main focus of this research is to identify how HR's role in designing, managing and delivering relevant content can strengthen Somethinc's brand positioning in the global market and increase its business competitiveness. Through a qualitative approach with interviews and case studies, this research reveals that the quality and creativity of human resources, understanding of international audiences, and the ability to adapt to digital trends play a very important role in formulating an effective content marketing strategy. Apart from that, solid team collaboration and the use of analytical data in decision making also support the achievement of more targeted marketing goals. The results of this research show that competent human resources can have a significant impact on increasing brand awareness and customer loyalty, which in turn strengthens Somethingnc's position in the international market. Therefore, investing in developing human resources who have digital skills and understanding of global markets is an important factor in a successful content marketing strategy.